Linguistic means of representing the flora in V. Svidzinsky's poetry (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article analyzes language means of expressing the flora at lexical-syntactical level. It has been discovered that nature always attracted the attention of the artist, it inspired and encouraged him. It has been a permanent companion to the writer's creativity. Whatever the poet portrayed, he always referred to the world around him, which correlated with his life, the natural surroundings. The research shows that phytonyms in V. Svidzinsky's poetic works, represented by various kinds and names, provide a bright insight into the space wherein the lyrical hero is located. Plants that are present in almost every writer’s poem are incorporated into a variety of syntactic constructions. They both act as active participants and perform a static function. To convey the beauty, refinement, uniqueness of nature, his attitude to flora, to identify the features of appearance, the behavior of characters V. Svidzinsky employs different structures of a sentence. The author uses simple sentences to achieve a laconic depiction of a specified space, he uses complex constructions to expand and generalize a thought, and he employs dialogue and direct speech to reproduce live oral speech. V. Svidzinsky often complicates the the above-mentioned constructions. To add some expressive tones to a narration the author uses separated attributives, to clarify and to detail the place and mode of action – separated adverbial modifiers of corresponding semantics; to specify the meaning of the aforementioned lexical units – the limiting parts of a sentence; to create a certain rhythmic-melodious and intonation contour of the text – repetitions; to emotionally emphasize a word or a word combination in the sentence – vocative; to give tension, liveliness, brightness, but sometimes also consistency or gradation to a speech – homogeneous parts of the sentence. Our observations proved that the latter are presented in V. Svydzinsky's poetry most vividly of all, and it is them that add richness, colorfulness, sophistication and perfection to the speech and emphasize the individual style of the author.
Keywords: individual style; simple, complex sentence; dialogue; direct speech; repetition; vocative